2020
DOI: 10.1111/1365-2745.13483
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil salinity on the expression of direct and indirect defences in wild cotton Gossypium hirsutum

Abstract: Previous studies have frequently reported effects of abiotic factors on herbivore‐induced plant defences based on effects on single plant traits. However, plants commonly express multiple defences simultaneously and these traits are often correlated. Thus, a fuller understanding of abiotic‐context dependency in plant defence requires measuring multiple traits and addressing their patterns of correlated expression. We evaluated the effects of soil salinity on the expression of direct (phenolic compounds, gossyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 94 publications
(142 reference statements)
0
7
0
Order By: Relevance
“…This result is in agreement with our expectations and also supports a previous study reporting that low water availability prevented the induction of VOCs by Camellia sinensis in response to exogenous application of methyl‐jasmonate (Scott et al, 2019). Relatedly, Quijano‐Medina et al (2021) found that soil salinization hampered the induction of phenolic compounds as well as a similar trend for some VOCs in wild cotton Gossypium hirsutum plants. Such effects of abiotic stress on the induction of VOCs can be explained by allocation costs associated with the synthesis and transport of plant secondary metabolites (Wilkinson et al, 2019).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This result is in agreement with our expectations and also supports a previous study reporting that low water availability prevented the induction of VOCs by Camellia sinensis in response to exogenous application of methyl‐jasmonate (Scott et al, 2019). Relatedly, Quijano‐Medina et al (2021) found that soil salinization hampered the induction of phenolic compounds as well as a similar trend for some VOCs in wild cotton Gossypium hirsutum plants. Such effects of abiotic stress on the induction of VOCs can be explained by allocation costs associated with the synthesis and transport of plant secondary metabolites (Wilkinson et al, 2019).…”
Section: Discussionmentioning
confidence: 88%
“…For example, recent work has shown that communication is strongly contingent upon the identity of the attacking herbivore, whereby resistance in receivers is only boosted when emitters and receivers are attacked by the same insect (Moreira et al, 2018). In addition, though much less studied, plant communication is likely contingent on abiotic factors such as soil nutrients, salinity or water availability, as these often affect plant defence induction in response to herbivory, including VOCs (Gouinguené & Turlings, 2002; Moreira et al, 2015; Quijano‐Medina et al, 2021; Sampedro et al, 2011; Suárez‐Vidal et al, 2019). There are at least two non‐exclusive mechanisms by which abiotic conditions could affect plant communication.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, chemotype-specific responses to caterpillar herbivory have been described in another species ( Tanacetum vulgare ) for both leaf-stored and emitted volatiles (Clancy et al, 2020). Despite being confined to coastal habitats, Yucatanese wild cotton is subjected to substantial spatial variability in herbivore pressure and abiotic conditions (Abdala-Roberts et al, 2019; Munguía-Rosas et al, 2019; Quijano-Medina et al, 2019, 2021), which could be associated with the origin of the observed variation in HIPVs. Further work is required to understand the drivers of these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Given the depletion of genetic diversity observed in modern cultivars of G. hirsutum (Yuan et al, 2021), exploring useful defensive traits in wild cotton should be considered. While volatile production in cultivated cotton has been well characterized, less is known about the volatiles produced by wild cotton (but see Loughrin et al, 1995; Hagenbucher et al, 2016; Quijano-Medina et al, 2021; Briones-May et al, 2023). G. hirsutum was domesticated at least 4,000 years ago in the Yucatán Peninsula (southeast Mexico) (Yuan et al, 2021), where wild populations still grow naturally along its northern coastline (Wegier et al, 2011; Coppens d’Eeckenbrugge and Lacape, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, studies have also shown that quantitative and qualitative variation in plant physical and chemical defences play an important role in determining the risk and intensity of herbivory (Feeny 1976;Marquis 1992), as well as in shaping insect herbivore communities (Richards et al 2015;Salazar et al 2016). Understanding these bottom-up effects of plant defences on phytophagous insects thus represents a fundamental challenge for explaining intra-and inter-specific variability in herbivory, one that also requires embracing the complex nature of plant defensive phenotypes by simultaneously studying multiple, often correlated, traits (Moreira et al 2020a;Quijano-Medina et al 2021).…”
Section: Introductionmentioning
confidence: 99%